"The Book of Negroes’ illustrated edition: circulating African-Canadian history through the Middlebrow" - Roberts, Gillian (University of Toronto Press, 2014)
This article examines the 2009 deluxe illustrated edition of Lawrence Hill’s Commonwealth Writers’ Prize– and Canada Reads–winning novel The Book of Negroes, originally published in 2007. It relates the story of Aminata, a West African girl kidnapped and sold into slavery, and her experiences on an indigo plantation in the American south, followed by further displacements to Charleston, Nova Scotia, Sierra Leone, and London. In New York, as the Revolutionary War comes to a close, Aminata becomes the scribe for the Book of Negroes, documenting the Black Loyalists, as well as the slaves and indentured servants of white Loyalists, granted passage by the British to Canada. Hill has commented that the Book of Negroes is an important document about which Canadians are largely ignorant. This desire to circulate knowledge about African-Canadian history through the novel is particularly manifest in the illustrated edition of 2009, where a photograph of the Book of Negroes features prominently, along with countless other images and captions which supplement and interrupt Hill’s narrative. This article considers the significance and implications of this “keepsake” or “souvenir” edition, particularly its circulation of knowledge about African-Canadian history through visual pleasure.